2018
DOI: 10.22159/ijap.2018.v10s1.57
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of the Effect of Nanostructured Lipid Carrier-Based Gel of Mulberry Root Extract Against Ultraviolet Light

Abstract: Objective: This study aimed to analyze the in vivo anti-ultraviolet (UV) activity of nanostructured lipid carrier (NLC) of mulberry extract on six New Zealand rabbits.Methods: Mulberry roots were treated with 96% ethanol using a maceration-ultrasonication method, and the extract was transformed into NLCs using the solvent evaporation method. The NLC was characterized for particle size and polydispersity index and zeta potential. The morphology of nanoparticles was examined using transmission electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…In vitro antioxidant activity of polysaccharides fractions obtained from M. alba leaves reported a significant free radical quenching potential (Liao et al, 2017). The anti‐ultraviolet activity of nanostructured lipid carrier mulberry root extract (96% ethanol)‐based gel preparation showed less protective effects on erythema in rabbits (Faizatun et al, 2018). The key findings of various in vivo and in vitro studies that indicated the antioxidant potential of the mulberry plant are in Table 5.…”
Section: Therapeutic Effectsmentioning
confidence: 99%
“…In vitro antioxidant activity of polysaccharides fractions obtained from M. alba leaves reported a significant free radical quenching potential (Liao et al, 2017). The anti‐ultraviolet activity of nanostructured lipid carrier mulberry root extract (96% ethanol)‐based gel preparation showed less protective effects on erythema in rabbits (Faizatun et al, 2018). The key findings of various in vivo and in vitro studies that indicated the antioxidant potential of the mulberry plant are in Table 5.…”
Section: Therapeutic Effectsmentioning
confidence: 99%